Electrophoretic deposition of zinc-doped hydroxyapatite coatings on titanium: deposition kinetics and coating morphology. (17th September 2019) - Moseke, Claus; Alramadan, Yunis Alnazal; Vorndran, Elke; Elter, Patrick
A wet chemistry reaction route was utilised to fabricate hydroxyapatite (HA) coatings with the incorporation of different amounts of zinc by electrophoretic deposition on titanium. HA powders and coatings were characterised by X-ray diffraction, scanning electron microscopy, and energy dispersive X-ray analysis. The presence of Zn had only a small impact on the crystallinity and practically no effect on the crystallite morphology of the powders and coatings. High additions of Zn apparently led to a change of the migration direction of the HA particles in the coating electrolyte and also resulted in increased crack formation during the drying process of the deposited coatings. Zn was incorporated in the HA coatings by ionic substitution and by incorporation of a low-crystalline ZnO phase, which may be advantageous for the application as a long-term reservoir for Zn as an osteoclast-inhibiting agent on biomaterials for implantation in critical bone situations.